The ethical contours of research in crisis settings: five practical considerations for academic institutional review boards and researchers. Issue 4 (22nd August 2019) - Falb, Kathryn; Laird, Betsy; Ratnayake, Ruwan; Rodrigues, Katherine; Annan, Jeannie
Abstract : The number of research studies in the humanitarian field is rising. It is imperative, therefore, that institutional review boards (IRBs) consider carefully the additional risks present in crisis contexts to ensure that the highest ethical standards are upheld. Ethical guidelines should represent better the specific issues inherent to research among populations grappling with armed conflict, disasters triggered by natural hazards, or health‐related emergencies. This paper seeks to describe five issues particular to humanitarian settings that IRBs should deliberate and on which they should provide recommendations to overcome associated challenges: staged reviews of protocols in acute emergencies; flexible reviews of modification requests; addressing violence and the traumatic experiences of participants; difficulties in attaining meaningful informed consent among populations dependent on aid; and ensuring reviews are knowledgeable of populations' needs. Considering these matters when reviewing protocols will yield more ethically sound research in humanitarian settings and hold researchers accountable to appropriate ethical standards.